1996
DOI: 10.2337/diacare.19.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Troglitazone: A new hypoglycemic agent in patients with NIDDM poorly controlled by diet therapy

Abstract: Troglitazone at 400 mg/day decreased FPG and HbA1c significantly in NIDDM patients who had failed to respond to diet therapy. Troglitazone, developed as a drug to enhance insulin action, can be a useful hypoglycemic agent for the treatment of NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(63 citation statements)
references
References 7 publications
4
54
0
5
Order By: Relevance
“…Meanwhile, many researchers have tried to standardize the criteria for defining the responders to TZD treatment with changing FPG or HbA 1c , and thus, the response rates of TZDs have been diversely reported [8,22]. However, since there are no standard cut-off criteria to define the responders to rosiglitazone treatment and for relatively short duration of our trial had been, we classified responders according to the criteria used by Iwamoto et al [8], and found a higher response rate, i.e., 75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, many researchers have tried to standardize the criteria for defining the responders to TZD treatment with changing FPG or HbA 1c , and thus, the response rates of TZDs have been diversely reported [8,22]. However, since there are no standard cut-off criteria to define the responders to rosiglitazone treatment and for relatively short duration of our trial had been, we classified responders according to the criteria used by Iwamoto et al [8], and found a higher response rate, i.e., 75%.…”
Section: Discussionmentioning
confidence: 99%
“…The thiazolidinedione (TZD) class of antidiabetic agents, such as rosiglitazone and pioglitazone, exert their insulin sensitizing effects on the peroxisome proliferators activated receptor (PPAR)␥ found in insulin-sensitive tissues such as adipose tissue, skeletal muscle, and liver [7][8][9][10][11]. Therefore, the glucose-lowering effects of the TZDs can be distinguished from the sulfonylureas, which act mainly by augmenting insulin secretion, and from the biguanides, which decrease gluconeogenesis and increase peripheral glucose utilization, requiring endogenous insulin to exert their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Upon ligand binding, PPARs form heterodimers with retinoid X receptor (RXR) and then bind to PPAR-responsive elements in the regulatory region of target genes. Thiazolidinediones (TZDs) are a group of PPARG agonists that are widely used in the treatment of type 2 diabetes [18,19]. Rosiglitazone, a representative TZD, is active in vivo as an anti-diabetic agent in the ob/ob mouse model, and has been used as an oral hypoglycaemic agent in the treatment of type 2 diabetes in humans for many years [20].…”
Section: Introductionmentioning
confidence: 99%
“…As in the animal studies, higher baseline BMI and the extent of hypertriglyceridemia predict a better improvement in HbA1c during Troglitazone treatment. 104 Also, the amount of subcutaneous fat and a gender effect (female better than male) have been shown to correlate positively with the TZD-induced improvement in HbA1c. 96,105 Hence, higher baseline BMI is likely to predict a higher weight gain during treatment.…”
Section: Ppargamma Agonistsfadipogenic Treatment Of Type II Diabetes mentioning
confidence: 99%